Exosomes and chronic rhinosinusitis. Issue 3 (1st September 2018) - Mueller, Sarina K.
Abstract : The objective of this manuscripts to review current knowledge regarding exosomes as they relate to the physiology and pathology of the human nose as well as their role as biomarkers of chronic rhinosinusitis with nasal polyps (CRSwNP). Exosomes are 30–150 nm membrane‐bound vesicles secreted by virtually all cell types. Exosomes contribute to the rapid inter‐epithelial transfer of proteins and mediate innate immunosurveillance and defense mechanisms in the human nasal cavity. Exosomes also protect their cell specific cargo from degradation by nucleases and proteases and mirrorCRS related tissue protein perturbations more effectively than whole mucus. Thus, exosomal isolation and analysis may be used to non‐invasively monitor disease severity, prognosis, and potentially even treatment response. Recent studies of exosomes in CRS suggest they can be used to study the immunopathology of chronic sinonasal inflammation. Furthermore, their relative accessibility suggests that exosomal proteomescan be used as non‐invasive, serial, and quantitative biosignatures for rhinosinusitis that can be sampled in clinic in order to predict disease severity, prognosis, and treatment response. Exosomal research has also led to important revelations regarding their physiologic function as they seem to play an important role in innate immunosurveillance and defense. However, exosomal research is still nascent and cost‐effectiveness as well as feasibility of implementation in the routine workup for CRS have to be further explored.